Answer: Option E is the correct answer; (1 + p⁴) / (1 + p³)
Step-by-step explanation:
P (3 head) = P(first and 3 heads) + P(second coin and 3 heads)
= (1/2)×1³ + (1/2)× p³ = (1/2) × (1 + p³)
therefore P(first coin given 3 heads) = (1/2)×1³/ ((1/2)×(1 + p³))
= 1 / (1 + p³)
Also P( second coin given 3 heads) = p³ /(1 + p³)
therefore P(4th toss in heads given first 3 are heads) will be;
= P(first and 4th toss heads) + P(second and 4th toss heads)
=(1/( 1 + p³ )) × 1 + p³ / (1+p³) × p
= (1 + p⁴) / (1 + p³)
Therefore Option E is the correct answer
Answer:
Yes
Step-by-step explanation:
I´m pretty sure but not 100% sure
X + y = 2
Substitute x + 8 into y
x + x + 8 = 2
2x + 8 =2
(Subtract 8 from both sides)
2x = -6
(Divide both sides by 2)
x = -3
Subsitute x = -3 into either equation to find y
x + y = 2
-3 + y = 2
(Add 3 to both sides)
y = 2 + 3
y = 5
Or y can be solved for using:
y = x + 8
y = -3 + 8
y = 5
Answer:
yes,this is congruent by SAS criteria
26 = 3x - 2 - 7x
26 + 2 = -4x
28 / -4 = x
x = -7
Best answer me please!